One chromosome, one contig: complete microbial genomes from long-read sequencing and assembly - Koren, Sergey; Phillippy, Adam M (Current opinion in microbiology, 2015)
•We describe three long-read sequencing technologies and their characteristics.•We describe available algorithms for long-read assembly and their use.•Most microbial genomes can now be automatically finished using long reads.•The total cost of finishing microbial genomes is now under $1000.•New methods are needed to assemble microbial populations and metagenomes. Like a jigsaw puzzle with large pieces, a genome sequenced with long reads is easier to assemble. However, recent sequencing technologies have favored lowering per-base cost at the expense of read length. This has dramatically reduced sequencing cost, but resulted in fragmented assemblies, which negatively affect downstream analyses and hinder the creation of finished (gapless, high-quality) genomes. In contrast, emerging long-read sequencing technologies can now produce reads tens of kilobases in length, enabling the automated finishing of microbial genomes for under $1000. This promises to improve the quality of reference databases and facilitate new studies of chromosomal structure and variation. We present an overview of these new technologies and the methods used to assemble long reads into complete genomes.